Ethnic disparities in the frequency of cancer reported in family histories. Issue 3 (28th March 2020) - Maves, Heather; Flodman, Pamela; Nathan, Deepika; Smith, Moyra
Abstract: This study was designed to observe whether disparities exist between ethnicities in reporting a family history of cancer in a cancer genetic counseling clinic. Four hundred sixty‐nine pedigrees collected between 2015 to 2017 from a cancer clinic at the University of California, Irvine, were analyzed. Pedigrees were separated by ethnicity into the following categories: non‐Hispanic White, Hispanic, Asian, or Ashkenazi Jewish. The number of first‐ and second‐degree relatives was calculated for each pedigree, and the total number of relatives reported with cancer. The total reported with cancer was divided by total number of relatives to derive a percentage of cancer reporting for each pedigree. The percentages of cancer reporting were analyzed using column proportions, nonparametric tests, and a Poisson regression. Cancer reporting in first‐ and second‐degree relatives was highest among non‐Hispanic Whites and Ashkenazi Jewish individuals, with median percentages of 22% and 27%, respectively. The median percentage of cancer reporting in first‐ and second‐degree relatives in both Hispanics and Asians was 10%. Cancer reporting medians were significantly lower in Hispanics and Asians when compared to non‐Hispanic Whites and Ashkenazi Jewish individuals ( p < .001). Ethnicity was a significant factor for predicting the number of relatives reported to have cancer when analyzed with a Poisson regression. This study concluded that cancer is reported less frequently in families when the proband and their families are Hispanic or Asian. Hispanics and Asians have lower cancer incidence rates; however, incidence rates alone may not explain the reporting disparity observed. Hence, family cancer histories in minority populations may be truncated. Healthcare professionals should be aware of this disparity when assessing cancer risks so appropriate modifications can be made accordingly for recommended cancer screening and/or cancer genetic testing. Further efforts are warranted to disseminate information to minority populations about the value of family health history regarding cancer risk assessment. Abstract :